Educação, desenvolvimento e ambiente: Por novas práticas pedagógicas para a Reserva Extrativista Chico Mendes - Maciel, Erinaldo Azevedo (Gestão de Áreas Protegidas da Amazônia – MPGAP, 2021)
This research addresses the education of the Elementary School I offered in the schools of the Chico Mendes Extractive Reserve, Acre, Brazil. Created in 1990, the area of this 970.5-thousand-hectare Conservation Unit (UC) covers the municipalities of Assis Brasil, Brasiléia, Capixaba, Epitaciolândia, Rio Branco, Seine Madureira and Xapuri. The contributions that school education can offer to families living in UCs were analyzed, considering the local reality and the social and environmental development. It seeks to understand the causes of recent and rapid socioeconomic and environmental transformations that occurred at Resex. The cultural changes of the families under study a little over a decade ago are notorious. But as everything evolves, culture also keeps evolving and this study aims to bring interactions with local education to seek a closer relationship between man and the environment. This should occur through a contextualized teaching process, where the student learns in school not only the contents proposed in the school curriculum. In order to achieve the objectives of the research, the main local economic activities that guarantee the socioeconomic development of the residents were identified. It was also analyzed how is the education offered by the public system and later, the subsidies for the innovation of the teaching practices and for the adaptation of the curriculum matrices of Resex schools. At this stage of the research two workshops were held involving representatives of the unit's managing bodies, non-governmental entities, educational institutions, teachers and community members. The methodology used revolved around the quantitative and qualitative research that started from the survey of the main sources of income of the residents and later with a bibliographical analysis about the theme studied through websites, magazines, books, articles, decrees, laws and documents. On-site research was also conducted through observation and interviews with semi-structured questionnaires. Finally, the holding of a workshop to discuss and insert subsidies to the pedagogical proposals of the UC schools. Keywords: Elementary school, contextualization, extractive reserve, environmental conservation.
Keywords: Educação; Resex Chico Mendes